The Use of Non-System Components of Construction Sets - KROTKÝ, JAN; KARPÍŠKOVÁ, PAVLA; KRÁL, JAN (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
The authors deal with an extension and modification of construction kits in order to create a simple tool for assessing the level of creativity according to the products made by pupils. The article describes a modified construction set – a creative set, divided into system and non-system parts. In the context of the product design, the use of non-system parts indicates the pupil‟s creativity performance. The creative set was tested out on a sample of 62 elementary school pupils. Subsequently, the authors put the products to analyse.